Development of biopellet formulation of Lecanicillium saksenae for the management of pepper root mealybug (Formicoccus polysperes) - SHARIN, ASNA; O P, REJI RANI (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2020–23 in the Biocontrol Laboratory for Crop Pest Management, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala. An indigenous isolate of Lecanicillium saksenae (Kushwaha) Kurihara and Sukarno, ITCC 7714 was assessed for its effectiveness against the pepper root mealybug (Formicoccus polysperes Williams). Peculiar symptoms like sudden dissolution of mealy coating subsequent to the application of conidial suspension and paralysis occurring 12 h post-treatment was observed in mealybugs upon infection. Its high potency to mealybug was established with its low LC50 value of 2.2 × 105 conidia/ml and its quick killing ability was proved with a lethal time of 23.13 h. Of the various carriers tested for pelleting, talc + chitin (95:5) was found to be the best as it exhibited highest conidial viability of 78.54%, 5-weeks after storage. Other carriers such as talc, chitin, chitosan and talc + chitosan (90:10) exhibited conidial viability of 33.96–74.58%. Among the different binding agents examined, the combination of talc + chitin (95:5) + carboxymethyl cellulose 6% was the superior one to maintain conidial viability to the tune of 80.63% when compared to microcrystalline cellulose 6% and acacia gum, Arabic 5% which exhibited 30.67–51.50% viability. The investigation therefore concluded that L. saksenae is a promising bioagent for the management of root mealybugs with high speed of action unlike the other microbes. Biopellets formulated at 109 conidia/ml using talc + chitin + 6% CMC at 15% moisture content were found to retain its viability and virulence during a storage period of three months, under ambient conditions.